Topological charge screening and the ‘proton spin’ beyond the chiral limit - Graham Shore (Nuclear Physics B, 1998)
The theory of the `proton spin' effect proposed in our earlier papers is extended to include the chiral SU(3) symmetry breaking and flavour mixing induced by non-vanishing quark masses in QCD. The theoretical basis is the derivation of exact, unified Goldberger-Treiman (GT) relations valid beyond the chiral limit. The observed suppression in the flavour singlet axial charge $a^0(Q^2)$ is explained by an anomalously small value for the slope of the singlet current correlation function $<0|T~\pl^\m J_{\m 5}^0 ~ \pl^\n J_{\n 5}^0 |0>$, a consequence of the screening of topological charge in the QCD vacuum. Numerical predictions are obtained by evaluating the current correlation functions using QCD spectral sum rules. The results, $a^0(Q^2) = 0.31 ± 0.02$ and $\int dx ~g_1^p(x,Q^2) = 0.141 ± 0.005$ (at $Q^2=10 G̃V^2$), are in good agreement with current experimental data on the polarised proton structure function